METHODS OF IMPROVING STUDENTS’ PHYSICAL ACTIVITY SKILLS IN EDUCATION INSTITUTIONS - Toirjonov Elyorbek Isakovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
It is to bring up a young generation in our country that is physically healthy, mature, well-rounded, well-rounded, able to think independently, has deep intellectual knowledge and a modern outlook, and can take responsibility for our future. Of course, one of the main factors influencing this is a healthy lifestyle.